2020
DOI: 10.1093/ibd/izaa036
|View full text |Cite
|
Sign up to set email alerts
|

The SPOSIB SB2 Sicilian Cohort: Safety and Effectiveness of Infliximab Biosimilar SB2 in Inflammatory Bowel Diseases, Including Multiple Switches

Abstract: Background No data on the recently introduced infliximab (IFX) biosimilar SB2 in inflammatory bowel disease (IBD) are available. Methods The Sicilian Prospective Observational Study of Patients With IBD Treated With Infliximab Biosimilar SB2 is a multicenter, observational, prospective study performed among the cohort of the Sicilian Network for Inflammatory Bowel Disease. All consecutive IBD patients starting the IFX biosimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 18 publications
10
38
0
Order By: Relevance
“…While various studies have investigated a switch from originator infliximab to the biosimilar CT-P13, so far there have been published data from only one cohort study of IBD patients in Italy (SPOSIB SB2) regarding treatment with SB2. 5 8 , 10 , 16 , 17 The analyses included 8 and 17 IBD patients switched from originator infliximab treatment to SB2, with a follow-up time of 6 and 18-months respectively; the majority of patients analyzed in the studied cohort were naïve to infliximab. 16 , 17 Based on the study results, overall safety and effectiveness of SB2 were estimated by the authors to be similar to those reported for originator infliximab and CT-P13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While various studies have investigated a switch from originator infliximab to the biosimilar CT-P13, so far there have been published data from only one cohort study of IBD patients in Italy (SPOSIB SB2) regarding treatment with SB2. 5 8 , 10 , 16 , 17 The analyses included 8 and 17 IBD patients switched from originator infliximab treatment to SB2, with a follow-up time of 6 and 18-months respectively; the majority of patients analyzed in the studied cohort were naïve to infliximab. 16 , 17 Based on the study results, overall safety and effectiveness of SB2 were estimated by the authors to be similar to those reported for originator infliximab and CT-P13.…”
Section: Discussionmentioning
confidence: 99%
“…The other study publication with a follow-up time of 18 months also included only a small fraction of patients that were switched from originator infliximab to SB2 (17 of 276), as nearly 70% of the analyzed patients were naïve to infliximab. 17 Assessment of safety was the primary endpoint of the study, with a total follow-up time of 182.7 person-years. Here, an SAE incidence rate of 36.7 per 100 person-years was recorded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the safety and efficacy of the infliximab biosimilar SB2 were similar to those reported for the infliximab originator and CT-P13, which switching patients who were in stable status showed relatively favourable clinical outcomes than those of naïve to infliximab patients. The study results also showed that biosilmilar to biosimlar switch or multiple switch groups were not significantly different in terms of treatment persistency compared to infliximab naïve or single switch groups [49] .…”
Section: Is Biosimilar To Biosimilar Infliximab Switch Safe?mentioning
confidence: 71%
“…Another one of the most recently published data came from The SPOSIB SB2 Sicilian Cohort [49] . It is a multicentre, observational, prospective study performed amongst the cohort of the Sicilian Network for IBD which included 276 patients (CD: 49.3%, UC: 50.7%).…”
Section: Is Biosimilar To Biosimilar Infliximab Switch Safe?mentioning
confidence: 99%